Preparation method of high-remanence neodymium-iron-boron magnet

Through the use of high-hydrogen content coarse powder and antioxidants that do not dehydrogenate after hydrogen crushing, combined with the secondary high-temperature sintering process, the problem of low residual magnetism of neodymium iron boron magnets is solved, and high residual magnetism and low cost industrial production is achieved .

CN119132820APending Publication Date: 2024-12-13JL MAG RARE EARTH CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411308482.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing sintered NdFeB magnets have problems such as complex process, high production costs and high total rare earths in improving residual magnetism, making it difficult to achieve large-scale production.

Method used

High-hydrogen content coarse powder that does not dehydrogenate after hydrogen crushing is adopted. The total amount of rare earth is reduced through formula design, and antioxidants are increased. Fine powder is prepared by airflow grinding and secondary high-temperature sintering is carried out to reduce oxygen content and impurity phases, thereby improving magnets. Density and remanent magnetism.

Benefits of technology

The residual magnetism of the sintered NdFeB magnet is achieved by exceeding 15.1KGs, which is simple in process and low in cost, suitable for mass production, and has good handling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049961870000011
    Figure BDA0005049961870000011
  • Figure BDA0005049961870000121
    Figure BDA0005049961870000121
  • Figure BDA0005049961870000122
    Figure BDA0005049961870000122
Patent Text Reader

Abstract

The invention provides the application of the non-dehydrogenation after hydrogen decrepitation treatment in the aspect of improving the residual magnetism of the neodymium-iron-boron magnet. The hydrogen content of the high-hydrogen-content coarse powder which is not dehydrogenated after the hydrogen decrepitation treatment is 1500-3500 ppm. According to the method, dehydrogenation treatment is not carried out especially in the hydrogen decrepitation treatment process, and the alloy coarse powder with high hydrogen content is obtained and used for improving the residual magnetism of the neodymium-iron-boron magnet. According to the preparation method of the high-remanence neodymium-iron-boron magnet, the production process is creatively designed and improved, the total amount of rare earth is reduced through formula design, the hydrogen content of coarse powder is increased, the coarse powder is sieved to remove impurities, an antioxidant is added into the coarse powder, and the measures of secondary high-temperature sintering and the like are adopted, so that the high-remanence neodymium-iron-boron magnet is obtained. And finally, the oxygen content of the magnet is reduced, namely, the beta non-ferromagnetic phase is reduced, and meanwhile, the density of the magnet is improved, so that the residual magnetism Br of the neodymium-iron-boron magnet is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sintered NdFeB magnet preparation, relates to the application of hydrogen crushing treatment without dehydrogenation in improving the remanence of NdFeB magnets and a method for preparing high remanence NdFeB magnets, and in particular to a method for preparing high remanence NdFeB magnets. Background Art

[0002] NdFeB magnet is made of neodymium, iron and boron (Nd2Fe 14 B) formed tetragonal crystals, NdFeB magnets are widely used in electronic products, automobiles, levitation trains, computers, machinery, etc. due to their excellent performance. With the continuous expansion of the new energy vehicle market, the miniaturization and high energy efficiency of motors have become new requirements. In order to ensure that the motor size is reduced as much as possible while maintaining the output power of the motor, the magnetic steel as the power core must have a high energy density, that is, high remanence. Professor Zhou Shouzeng and others gave the calculation formula of remanence in the book "Sintered NdFeB Permanent Magnet Materials and Technology":

[0003]

[0004] Where A is the volume fraction of the positive domain, β is the volume fraction of the non-ferromagnetic phase, dmagnet is the actual magnet density, dprinciple is the theoretical magnet density, cosθ is the orientation degree, and Js is the magnetic polarization intensity. Theoretically, the ultimate remanence of pure NdFeB magnets is 16.1 kGs. At present, the highest remanence that can be obtained under laboratory conditions is 15.55 kGs, but due to process difficulty and equipment accuracy, it is far from enough to achieve mass production.

[0005] At present, the main methods to improve the remanence of sintered NdFeB magnets are: ①Increasing the Nd2Fe 14① The volume fraction of B (T1) phase is reduced by reducing β, that is, reducing defects such as oxidation and impurities of the magnet (including reducing other impurities such as Nd-rich phase, B-rich phase, Nd2O3 phase, etc.); ② Increasing the orientation degree cosθ of T1 phase grains; ③ Increasing the relative density of the magnet (dmagnet / dmagnet). Conventional methods to increase the volume fraction of T1 phase include reducing the total amount of rare earth and reducing impurity phases. Among them, reducing the total amount of rare earth needs to be considered in the composition design process, reducing the impurity phase requires the design of the process technology, and the production process must be strictly controlled according to the process. For example, a Chinese patent with application number 202011094313.X discloses a method for preparing a high remanence sintered NdFeB magnet. This method mainly achieves the purpose of increasing the remanence of the magnet (remanence is 15.07kGs-15.18kGs) by increasing the T1 phase grain orientation degree cosθ through two pressing processes (initial pressing and secondary pressing). The total amount of rare earth is 29.2wt%, but the total amount of rare earth in this scheme is high, and two moldings are required. The production process is complicated and the production cost is high, which is not conducive to mass production.

[0006] Therefore, how to find a more suitable preparation method for high remanence sintered NdFeB magnets, solve the above problems existing in the existing NdFeB magnets, and improve the remanence of sintered NdFeB magnets has become one of the urgent problems to be solved by many manufacturers and researchers in the industry. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide an application of hydrogen crushing treatment without dehydrogenation in improving the remanence of NdFeB magnets and a method for preparing a high remanence NdFeB magnet. The preparation method provided by the present invention can improve the remanence of the magnet, and the remanence of the sintered NdFeB magnet obtained thereby is greater than 15.1KGs. At the same time, the process is simple, the conditions are mild, and the controllability is good, which is more suitable for the promotion and application of industrial production.

[0008] The present invention provides an application of hydrogen crushing treatment without dehydrogenation in improving the remanence of NdFeB magnets;

[0009] The hydrogen content of the coarse powder with high hydrogen content that is not dehydrogenated after the hydrogen crushing treatment is 1500 to 3500 ppm.

[0010] Preferably, the application also includes the application of reducing the total amount of rare earth in magnets to improve the remanence of NdFeB magnets;

[0011] The total mass content of rare earth in the raw materials of the magnet is less than or equal to 29%;

[0012] The application also includes the application of the secondary sintering method in improving the remanence of NdFeB magnets;

[0013] In the secondary sintering method, the temperature of the second sintering is 1060-1090°C;

[0014] The second sintering time is 3 to 8 hours.

[0015] Preferably, the application also includes increasing the particle size of the fine powder and adding an antioxidant when preparing the fine powder to increase the remanence of the NdFeB magnet;

[0016] The method of preparing fine powder is jet milling;

[0017] The median particle size of the fine powder is greater than or equal to 4.5 μm;

[0018] The added amount of the antioxidant is 0.04% to 0.1%.

[0019] The present invention provides a method for preparing a high remanence NdFeB magnet, comprising the following steps:

[0020] 1) The magnet raw material is smelted and cast into alloy flakes;

[0021] The total mass content of rare earth in the magnet raw material is less than or equal to 29%;

[0022] 2) subjecting the alloy flakes obtained in the above steps to hydrogen crushing without dehydrogenation to obtain a coarse powder with a high hydrogen content;

[0023] 3) mixing the coarse powder with high hydrogen content obtained in the above step, a lubricant and an antioxidant, and then jet milling the mixture to obtain a fine powder;

[0024] 4) orienting and pressing the fine powder obtained in the above steps to obtain a green compact;

[0025] 5) The green compact obtained in the above steps is subjected to a first sintering and a second sintering to obtain a high remanence NdFeB magnet.

[0026] Preferably, the magnet raw material, measured by mass percentage, includes:

[0027] Nd: 27% to 29%, Co: 0 to 1%, Cu: 0 to 0.5%, B: 0.85% to 1.0%, Zr: 0 to 0.5% and the balance Fe;

[0028] The hydrogen content of the coarse powder with high hydrogen content is 1500-3500 ppm.

[0029] Preferably, the lubricant comprises zinc stearate;

[0030] The mass ratio of the lubricant to the coarse powder is (0.04-0.1):100;

[0031] The antioxidant includes hexadecane-D34;

[0032] The mass ratio of the antioxidant to the coarse powder is (0.04-0.1):100.

[0033] Preferably, the median particle size of the fine powder is 4.5 to 6.0 μm;

[0034] The magnitude of the oriented magnetic field is 16000 to 22000 Gs;

[0035] The pressure of the compression molding is 100-240 MPa.

[0036] Preferably, the vacuum pressure of the first sintering is (2-8)×10 -2 Pa;

[0037] The temperature of the first sintering is 1050-1070°C;

[0038] The first sintering time is 3 to 10 hours.

[0039] Preferably, the vacuum pressure of the second sintering is (2-8)×10 -2 Pa;

[0040] The temperature of the second sintering is 1060-1090°C;

[0041] The second sintering time is 3 to 8 hours.

[0042] After the second sintering, the process further includes primary aging and secondary aging treatment steps;

[0043] The primary aging temperature is 850-950°C;

[0044] The primary aging time is 3 to 5 hours;

[0045] The temperature of the secondary aging is 440-560°C;

[0046] The secondary aging time is 3 to 6 hours.

[0047] The present invention provides an application of hydrogen crushing treatment without dehydrogenation in improving the remanence of NdFeB magnets; the hydrogen content of the high hydrogen content coarse powder without dehydrogenation after hydrogen crushing treatment is 1500-3500ppm. Compared with the prior art, the present invention does not perform dehydrogenation treatment during the hydrogen crushing treatment to obtain a high hydrogen content alloy coarse powder, and creatively uses it to improve the remanence of NdFeB magnets. The present invention correspondingly provides a preparation method of a high remanence NdFeB magnet, which creatively designs and improves the production process, reduces the total amount of rare earth by formula design, improves the hydrogen content of the coarse powder, sieves the coarse powder to remove impurities, adds an antioxidant to the coarse powder, and adopts secondary high-temperature sintering and other measures, ultimately reducing the oxygen content of the magnet, that is, reducing the β non-ferromagnetic phase, while increasing the density of the magnet, thereby effectively increasing the remanence Br of the NdFeB magnet.

[0048] The invention provides a method for preparing a high remanence sintered NdFeB magnet, and the high remanence is achieved specifically through the following ways: 1. the total amount of rare earth is reduced by formula design, and the total amount of rare earth is less than 29wt%, which is equivalent to reducing the Nd-rich phase, that is, reducing β, thereby improving the remanence; 2. hydrogenation is not removed after hydrogenation (hydrogen is removed in the subsequent sintering process), so that the magnetic powder is not easily oxidized to generate Nd2O3 during the circulation process, that is, reducing β, thereby improving the remanence; 3. coarse powder is screened to screen out impurity phases and hydrogenation abnormal casting flakes, that is, reducing β, thereby improving the remanence; 4. antioxidant is added in the air flow mill, and the median diameter of the powder is increased to more than 4.5μm at the same time. The larger the diameter of the powder is, the smaller the specific surface area is, and the less likely it is to be oxidized, thereby reducing the risk of powder particles being oxidized to generate Nd2O3 during the circulation process, that is, reducing β, thereby improving the remanence; 5. a secondary high-temperature sintering process is adopted to increase the density of the magnet, thereby improving the remanence.

[0049] The remanence of the sintered NdFeB magnet prepared by the present invention is greater than 15.1 KGs, the production cost is low, the process is simple, the conditions are mild, and the controllability is good, which is more suitable for promotion and application of mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 A schematic diagram of the production process of the method for preparing the high remanence NdFeB magnet provided by the present invention;

[0051] Figure 2 This is a photo of the appearance of the magnet prepared in Comparative Example 1 of the present invention (oxidation deformation);

[0052] Figure 3 This is a photograph of the appearance of the magnet prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0053] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0054] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0055] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses industrial purity or conventional purity used in the field of NdFeB magnets.

[0056] The present invention provides an application of hydrogen crushing treatment without dehydrogenation in improving the remanence of NdFeB magnets;

[0057] The hydrogen content of the coarse powder with high hydrogen content that is not dehydrogenated after the hydrogen crushing treatment is 1500-3500 ppm, can be 1900-3100 ppm, and can be 2300-2700 ppm.

[0058] In the present invention, the application also preferably includes the application of reducing the total amount of rare earth in the magnet to improve the remanence of the NdFeB magnet.

[0059] In the present invention, the total mass content of rare earth in the raw material of the magnet is preferably less than or equal to 29%, more preferably less than or equal to 28.9%, more preferably less than or equal to 28.8%, more preferably less than or equal to 28.7%.

[0060] In the present invention, the application also preferably includes the application of a secondary sintering method in improving the remanence of NdFeB magnets.

[0061] In the present invention, in the secondary sintering method, the temperature of the second sintering is preferably 1060-1090°C, more preferably 1065-1085°C, and more preferably 1070-1080°C.

[0062] In the present invention, the second sintering time is preferably 3 to 8 hours, more preferably 4 to 7 hours, and more preferably 5 to 6 hours.

[0063] In the present invention, the application also preferably includes increasing the particle size of the fine powder and adding an antioxidant when preparing the fine powder to increase the remanence of the NdFeB magnet.

[0064] In the present invention, the method for preparing fine powder is preferably air jet milling.

[0065] In the present invention, the median particle size of the fine powder is preferably greater than or equal to 4.5 μm, more preferably greater than or equal to 5.0 μm, and specifically may be 4.5 to 8 μm, or 5.0 to 7 μm, or 5.5 to 6.5 μm.

[0066] In the present invention, the added amount of the antioxidant is preferably 0.04% to 0.1%, more preferably 0.05% to 0.09%, and more preferably 0.06% to 0.08%.

[0067] The present invention provides a method for preparing a high remanence NdFeB magnet, comprising the following steps:

[0068] 1) The magnet raw material is smelted and cast into alloy flakes;

[0069] The total mass content of rare earth in the magnet raw material is less than or equal to 29%;

[0070] 2) subjecting the alloy flakes obtained in the above steps to hydrogen crushing without dehydrogenation to obtain a coarse powder with a high hydrogen content;

[0071] 3) mixing the coarse powder with high hydrogen content obtained in the above step, a lubricant and an antioxidant, and then jet milling the mixture to obtain a fine powder;

[0072] 4) orienting and pressing the fine powder obtained in the above steps to obtain a green compact;

[0073] 5) The green compact obtained in the above steps is subjected to a first sintering and a second sintering to obtain a high remanence NdFeB magnet.

[0074] The present invention firstly melts the magnet raw material into a casting sheet to obtain an alloy casting sheet;

[0075] In the magnet raw material, the total mass content of rare earth is preferably less than or equal to 29%, more preferably less than or equal to 28%, and more preferably less than or equal to 27.5%.

[0076] In the present invention, the magnet raw material preferably includes, by mass percentage:

[0077] Nd: 27% to 29%, Co: 0 to 1%, Cu: 0 to 0.5%, B: 0.85% to 1.0%, Zr: 0 to 0.5% and the balance Fe, more preferably Nd: 27.4% to 28.6%, Co: 0.2 to 0.8%, Cu: 0.1 to 0.4%, B: 0.88% to 0.97%, Zr: 0.1 to 0.4%, more preferably Nd: 27.8% to 28.2%, Co: 0.4 to 0.6%, Cu: 0.2 to 0.3%, B: 0.91% to 0.94%, Zr: 0.2 to 0.3%.

[0078] The present invention further performs hydrogen crushing treatment on the alloy casting flakes obtained in the above steps without dehydrogenation to obtain coarse powder with high hydrogen content.

[0079] In the present invention, the hydrogen content of the coarse powder with a high hydrogen content is preferably 1500 to 3500 ppm, more preferably 1900 to 3100 ppm, and even more preferably 2300 to 2700 ppm.

[0080] The present invention then mixes the coarse powder with high hydrogen content obtained in the above steps, lubricant and antioxidant, and then performs jet milling to obtain fine powder.

[0081] In the present invention, the lubricant preferably includes zinc stearate.

[0082] In the present invention, the mass ratio of the lubricant to the coarse powder is preferably (0.04-0.1):100, more preferably (0.05-0.09):100, and more preferably (0.06-0.08):100.

[0083] In the present invention, the antioxidant preferably includes hexadecane-D34.

[0084] In the present invention, the mass ratio of the antioxidant to the coarse powder is preferably (0.04-0.1):100, more preferably (0.05-0.09):100, and more preferably (0.06-0.08):100.

[0085] In the present invention, the median particle size of the fine powder is preferably 4.5 to 6.0 μm, more preferably 4.8 to 5.7 μm, and more preferably 5.1 to 5.4 μm.

[0086] The present invention then orients and presses the fine powder obtained in the above steps to obtain a compact.

[0087] In the present invention, the magnitude of the oriented magnetic field is preferably 16000 to 22000 Gs, more preferably 17000 to 21000 Gs, and even more preferably 18000 to 20000 Gs.

[0088] In the present invention, the pressure of the press molding is preferably 100 to 240 MPa, more preferably 130 to 210 MPa, and even more preferably 160 to 170 MPa.

[0089] In the present invention, the compact obtained in the above steps is finally sintered for the first time and the second time to obtain a high remanence NdFeB magnet.

[0090] In the present invention, the vacuum pressure of the first sintering is preferably (2-8)×10 -2 Pa, more preferably (3 to 7)×10 -2 Pa, more preferably (4 to 6)×10 -2 Pa.

[0091] In the present invention, the temperature of the first sintering is preferably 1050-1070°C, more preferably 1054-1066°C, and more preferably 1058-1062°C.

[0092] In the present invention, the first sintering time is preferably 3 to 10 hours, more preferably 4 to 9 hours, more preferably 5 to 8 hours, and more preferably 6 to 7 hours.

[0093] In the present invention, the vacuum pressure of the second sintering is preferably (2-8)×10 -2 Pa, more preferably (3 to 7)×10 -2 Pa, more preferably (4 to 6)×10 -2 Pa.

[0094] In the present invention, the temperature of the second sintering is preferably 1060-1090°C, more preferably 1065-1085°C, and more preferably 1070-1080°C.

[0095] In the present invention, the second sintering time is preferably 3 to 8 hours, more preferably 4 to 7 hours, and more preferably 5 to 6 hours.

[0096] In the present invention, there is a cooling process between the two sinterings. There are two schemes for the cooling process: ① After the first sintering, the temperature is cooled to 700°C, and then the temperature is raised to the second sintering temperature; ② After the first sintering is completed and cooled to room temperature (5-40°C), the temperature is raised to the second sintering temperature. Relatively speaking, the first scheme takes a short time and saves sintering time.

[0097] In the present invention, after the second sintering, it is preferred to further include primary aging and secondary aging treatment steps.

[0098] In the present invention, the primary aging temperature is preferably 850-950°C, more preferably 870-930°C, and more preferably 890-910°C.

[0099] In the present invention, the primary aging time is preferably 3 to 5 hours, more preferably 3.4 to 4.6 hours, and more preferably 3.8 to 4.2 hours.

[0100] In the present invention, the temperature of the secondary aging is preferably 440-560°C, more preferably 460-540°C, and more preferably 480-520°C.

[0101] In the present invention, the secondary aging time is preferably 3 to 6 hours, more preferably 3.5 to 5.5 hours, and more preferably 4 to 5 hours.

[0102] See also Figure 1 , Figure 1The present invention provides a simplified schematic diagram of the production process of the method for preparing the high remanence NdFeB magnet.

[0103] The present invention is to complete and refine the overall technical solution, better ensure the structure and characteristics of the NdFeB magnet, and further improve the remanence of the NdFeB magnet. The application of the above-mentioned hydrogen crushing treatment without dehydrogenation in improving the remanence of the NdFeB magnet and a method for preparing a high remanence NdFeB magnet can specifically include the following contents:

[0104] A method for preparing a neodymium iron boron magnet comprises the following steps:

[0105] a. Formula design: Prepare the raw materials required for the preparation of NdFeB magnets according to the following mass percentages: Nd: 27% to 29%; Co: 0 to 1%; Cu: 0 to 0.5%; B: 0.85% to 1.0%; Zr: 0 to 0.5%; Fe: balance.

[0106] b. Melting: adding the raw materials prepared in step a into a vacuum melting furnace, melting by a rapid solidification casting method, the casting temperature during the melting process is 1440-1480° C., and preparing alloy castings with a thickness of 0.2-0.45 mm;

[0107] c. Hydrogen crushing: adding the alloy flakes obtained in step b into a hydrogen crushing furnace and carrying out hydrogen crushing by adopting a low-temperature hydrogen absorption method, without dehydrogenation treatment in this process, to obtain a coarse powder with a high hydrogen content;

[0108] d. Airflow milling: The coarse powder obtained in step c is sieved through a 10-40 mesh screen to remove impurities and hydrogen-fragmented abnormal flakes, and then 0.04% to 0.1% by weight of a lubricant and 0.04% to 0.1% by weight of an antioxidant are added to the coarse powder, wherein the lubricant is zinc stearate and the antioxidant is hexadecane-D34, and after stirring evenly, the powder is pulverized by airflow milling to prepare a fine powder with a median diameter of more than 4.5 μm;

[0109] e. Pressing: Pressing the fine powder obtained in step d into a green compact by magnetic field orientation, wherein the orientation magnetic field is 16000 Gs to 22000 Gs.

[0110] f. Sintering: The green body obtained in step e is further subjected to isostatic pressing at a pressure of 100-240 MPa, and then placed in a vacuum sintering furnace for sintering. The sintering is carried out under vacuum conditions, and the vacuum degree of the sintering is (2-8)×10 -2Pa, the primary high-temperature sintering temperature is 1050-1070°C, the sintering time is 3-10h, the secondary high-temperature sintering temperature is 1060-1090°C, the sintering time is 3-8h, and then cooling is performed, followed by primary aging and secondary aging. The primary aging temperature is preferably 850-950°C, and the time is 3-5h; the secondary aging temperature is 440-560°C, and the time is 3-6h;

[0111] g. Performance testing: Perform magnetic performance testing on the NdFeB magnet obtained in step f.

[0112] The above content of the present invention provides the application of not dehydrogenating after hydrogen crushing treatment in improving the remanence of NdFeB magnets and a method for preparing a high remanence NdFeB magnet. In particular, the present invention does not perform dehydrogenation treatment during the hydrogen crushing process to obtain a coarse alloy powder with a high hydrogen content, and creatively uses it to improve the remanence of NdFeB magnets. The present invention correspondingly provides a method for preparing a high remanence NdFeB magnet, which creatively designs and improves the production process, reduces the total amount of rare earth by formula design, increases the hydrogen content of the coarse powder, sieves the coarse powder to remove impurities, adds an antioxidant to the coarse powder, and adopts secondary high-temperature sintering and other measures, ultimately reducing the oxygen content of the magnet, that is, reducing the β non-ferromagnetic phase, while increasing the density of the magnet, thereby effectively increasing the remanence Br of the NdFeB magnet.

[0113] The invention provides a method for preparing a high remanence sintered NdFeB magnet, and the high remanence is achieved specifically through the following ways: 1. the total amount of rare earth is reduced by formula design, and the total amount of rare earth is less than 29wt%, which is equivalent to reducing the Nd-rich phase, that is, reducing β, thereby improving the remanence; 2. hydrogenation is not removed after hydrogenation (hydrogen is removed in the subsequent sintering process), so that the magnetic powder is not easily oxidized to generate Nd2O3 during the circulation process, that is, reducing β, thereby improving the remanence; 3. coarse powder is screened to screen out impurity phases and hydrogenation abnormal casting flakes, that is, reducing β, thereby improving the remanence; 4. antioxidant is added in the air flow mill, and the median diameter of the powder is increased to more than 4.5μm at the same time. The larger the diameter of the powder is, the smaller the specific surface area is, and the less likely it is to be oxidized, thereby reducing the risk of powder particles being oxidized to generate Nd2O3 during the circulation process, that is, reducing β, thereby improving the remanence; 5. a secondary high-temperature sintering process is adopted to increase the density of the magnet, thereby improving the remanence.

[0114] The remanence of the sintered NdFeB magnet prepared by the present invention is greater than 15.1 KGs, the production cost is low, the process is simple, the conditions are mild, and the controllability is good, which is more suitable for promotion and application of mass production.

[0115] In order to further illustrate the present invention, the application of the hydrogen crushing treatment without dehydrogenation provided by the present invention in improving the remanence of NdFeB magnets and a method for preparing a high remanence NdFeB magnet are described in detail below in combination with the examples. However, it should be understood that these examples are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.

[0116] Example 1

[0117] The ingredients are prepared according to Table 1 (mass percentage):

[0118] Table 1 Details of ingredients in Example 1

[0119] element Nd B Co Cu Zr Ga Fe Content (wt%) 28.7 0.92 0.5 0.1 0.1 0.1 margin

[0120] The prepared raw materials are added into a vacuum melting furnace, and the melting is carried out by the rapid solidification casting method. The casting temperature during the melting process is 1450°C, and an alloy casting sheet with a thickness of 0.20-0.35mm is prepared; the obtained alloy casting sheet is added into a hydrogen crushing furnace, and hydrogen crushing is carried out by low-temperature hydrogen absorption, and coarse powder is obtained without dehydrogenation. The hydrogen content of the coarse powder is tested to be 2450ppm; the obtained coarse powder is sieved with a 10-mesh screen to screen out impurities and hydrogen-fragmented abnormal casting sheets, and then 0.06wt% by weight of the coarse powder is added The invention discloses a method for preparing a green body by isostatic pressing at a pressure of 200 MPa and then placing the green body in a vacuum sintering furnace for sintering. The sintering is carried out under vacuum conditions, and the vacuum degree of the sintering is 6×10 -2 Pa, the temperature of the first high-temperature sintering is 1065°C, and the sintering time is 6h, the temperature of the second high-temperature sintering is 1075°C, and the sintering time is 6h, followed by cooling and sequentially performing primary aging and secondary aging. The temperature of the primary aging is preferably 890°C, and the time is 3h; the temperature of the secondary aging is 520°C, and the time is 5h; according to GB / T-3217-2-13 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials", the magnetic properties of the NdFeB magnets prepared in the embodiments of the present invention are tested, and the test results are shown in Table 6.

[0121] Example 2

[0122] The ingredients are prepared according to Table 2 (mass percentage):

[0123] Table 2 Details of ingredients in Example 2

[0124] element Nd B Co Cu Zr Ga Fe Content (wt%) 28.7 0.92 0.5 0.1 0.1 0.1 margin

[0125] The prepared raw materials are added into a vacuum melting furnace, and the melting is carried out by the rapid solidification casting method. The casting temperature during the melting process is 1450°C, and an alloy casting sheet with a thickness of 0.20-0.35 mm is prepared; the obtained alloy casting sheet is added into a hydrogen crushing furnace, and hydrogen crushing is carried out by low-temperature hydrogen absorption, and coarse powder is obtained without dehydrogenation. The hydrogen content of the coarse powder is tested to be 2430ppm; the obtained coarse powder is sieved with a 10-mesh screen to screen out impurities and hydrogen-fragmented abnormal casting sheets, and then 0.06wt% by weight of the coarse powder is added The invention discloses a method for preparing a green body by isostatic pressing at a pressure of 200 MPa and then placing the green body in a vacuum sintering furnace for sintering. The sintering is carried out under vacuum conditions, and the vacuum degree of the sintering is 6×10 -2 Pa, the temperature of the first high-temperature sintering is 1065°C, and the sintering time is 6h, the temperature of the second high-temperature sintering is 1075°C, and the sintering time is 6h, followed by cooling and sequentially performing primary aging and secondary aging. The temperature of the primary aging is preferably 890°C, and the time is 3h; the temperature of the secondary aging is 520°C, and the time is 5h; according to GB / T-3217-2-13 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials", the magnetic properties of the NdFeB magnets prepared in the embodiments of the present invention are tested, and the test results are shown in Table 6.

[0126] Example 3

[0127] The ingredients are prepared according to Table 3 (mass percentage):

[0128] Table 3 Details of ingredients in Example 3

[0129] element Nd B Co Cu Zr Ga Fe Content (wt%) 28.7 0.92 0.5 0.1 0.1 0.1 margin

[0130] The prepared raw materials were added into a vacuum melting furnace, and the melting was carried out by the rapid solidification casting method. The casting temperature during the melting process was 1450°C, and an alloy casting with a thickness of 0.20-0.35 mm was prepared; the obtained alloy casting was added into a hydrogen crushing furnace, and hydrogen was absorbed and crushed by low temperature without dehydrogenation to obtain a coarse powder. The hydrogen content of the coarse powder was 2470ppm; the obtained coarse powder was sieved with a 10-mesh screen to screen out impurities and hydrogen-fragmented castings, and then 0.06wt% of the weight of lubricant was added to the obtained coarse powder. The obtained fine powder is subjected to magnetic field orientation pressing to form a green body, wherein the orientation magnetic field size is 19000 Gs; the obtained green body is subjected to isostatic pressing at a pressure of 200 MPa, and then placed in a vacuum sintering furnace for sintering, and the sintering is carried out under vacuum conditions, and the vacuum degree of the sintering is 6×10 -2 Pa, the temperature of the first high-temperature sintering is 1065°C, and the sintering time is 6h, the temperature of the second high-temperature sintering is 1075°C, and the sintering time is 6h, followed by cooling and sequentially performing primary aging and secondary aging. The temperature of the primary aging is preferably 890°C, and the time is 3h; the temperature of the secondary aging is 520°C, and the time is 5h; according to GB / T-3217-2-13 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials", the magnetic properties of the NdFeB magnets prepared in the embodiments of the present invention are tested, and the test results are shown in Table 6.

[0131] Comparative Example 1

[0132] The ingredients (mass percentage) are prepared according to Table 4, which are consistent with those in Examples 1 to 3:

[0133] Table 4 Details of ingredients in comparative example 1

[0134] element Nd B Co Cu Zr Ga Fe Content (wt%) 28.7 0.92 0.5 0.1 0.1 0.1 margin

[0135] The prepared raw materials were added into a vacuum melting furnace, and the melting was carried out by a rapid solidification casting method. The casting temperature during the melting process was 1450°C, and an alloy casting sheet with a thickness of 0.20-0.35 mm was prepared; the obtained alloy casting sheet was added into a hydrogen crushing furnace, and hydrogen crushing was carried out by low-temperature hydrogen absorption, and then dehydrogenation treatment was carried out at 580°C for 6 hours. The hydrogen content of the coarse powder after dehydrogenation was tested to be 830ppm; then 0.06wt% lubricant was added to the obtained coarse powder, and the lubricant was zinc stearate. After stirring evenly, the powder was powdered by air flow grinding to prepare a fine powder with a median diameter of 4.2μm; the obtained fine powder was magnetic field oriented and pressed to form a green body, wherein the orientation magnetic field size was 19000Gs; the obtained green body was isostatically pressed at a pressure of 200MPa, and then placed in a vacuum sintering furnace for sintering. The sintering was carried out under vacuum conditions, and the vacuum degree of the sintering was 6×10-2 Pa, the temperature of the first high-temperature sintering is 1065°C, the sintering time is 6h, and then cooling is carried out in sequence for primary aging and secondary aging. The temperature of the primary aging is preferably 890°C, and the time is 3h; the temperature of the secondary aging is 520°C, and the time is 5h. According to GB / T-3217-2-13 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials", the magnetic properties of the NdFeB magnets prepared in the embodiments of the present invention are tested, and the test results are shown in Table 6.

[0136] The production process comparison between the embodiment and the comparative example is shown in Table 5:

[0137] Table 5 Comparison of production processes of the embodiment and the comparative example

[0138]

[0139] The magnetic properties, oxygen content and density of the embodiments and comparative examples are shown in Table 6 below:

[0140] Table 6 Magnetic properties test results of NdFeB magnets prepared in Examples and Comparative Examples

[0141]

[0142] From the analysis of the test data of Examples 1 to 3 and Comparative Example 1 in Table 6, it can be seen that under the condition of the same composition, the present invention reduces the oxygen content of the magnet and increases the density of the magnet by improving the production process (increasing the hydrogen content, sieving the coarse powder to remove impurities, adding antioxidants, and adopting secondary high-temperature sintering), thereby increasing the remanence of the magnet.

[0143] At the same time, the present invention found that the magnet of comparative example 1 showed bending deformation after sintering ( Figure 2 ), Example 1 did not show bending deformation ( Figure 3 ), and the oxygen content of the magnet was found to be 256ppm higher than that of the embodiment (as shown in Table 6), which was inferred to be caused by the low rare earth content and the oxygen absorption of the powder particles during the circulation process, indicating that: 1. In the embodiment, the coarse powder is not dehydrogenated, the coarse powder is added with an antioxidant, and the median particle size of the fine powder reaches 4.5μm or more, which can effectively reduce the oxygen content of the magnet, prevent the magnet from oxidizing and deforming, and ultimately improve the magnet performance; 2. At the current technological level, the magnet is designed with a low total amount of rare earth. If the process protection is not in place, the magnet will eventually oxidize and deform, and a magnet with high remanence will not be obtained. It can be seen that the preparation method of the present invention can effectively improve the remanence of the magnet.

[0144] See also Figure 2 , Figure 2 This is a photograph of the appearance of the magnet prepared in Comparative Example 1 of the present invention (oxidation deformation).

[0145] See also Figure 3 , Figure 3 This is a photograph of the appearance of the magnet prepared in Example 1 of the present invention.

[0146] The above is a detailed introduction to the application of the present invention provided by the present invention in improving the remanence of NdFeB magnets without dehydrogenation after hydrogen crushing treatment and a method for preparing a high remanence NdFeB magnet. The principle and implementation method of the present invention are described in detail using specific examples. The description of the above embodiments is only used to help understand the method and its core idea of ​​the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in several ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the textual expression of the claims, or if they include equivalent structural elements that are not substantially different from the textual expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. Application of hydrogen crushing treatment without dehydrogenation in improving the remanence of NdFeB magnets; The hydrogen content of the coarse powder with high hydrogen content that is not dehydrogenated after the hydrogen crushing treatment is 1500 to 3500 ppm.

2. The use according to claim 1, characterized in that: The application also includes the application of reducing the total amount of rare earth in magnets to improve the remanence of NdFeB magnets; The total mass content of rare earth in the raw materials of the magnet is less than or equal to 29%; The application also includes the application of the secondary sintering method in improving the remanence of NdFeB magnets; In the secondary sintering method, the temperature of the second sintering is 1060-1090°C; The second sintering time is 3 to 8 hours.

3. The use according to claim 1, characterized in that: The application also includes increasing the particle size of fine powder and adding antioxidants when preparing fine powder to increase the remanence of NdFeB magnets; The method of preparing fine powder is jet milling; The median particle size of the fine powder is greater than or equal to 4.5 μm; The added amount of the antioxidant is 0.04% to 0.1%.

4. A method for preparing a high remanence NdFeB magnet, characterized in that: The following steps are involved: 1) The magnet raw material is smelted and cast into alloy flakes; The total mass content of rare earth in the magnet raw material is less than or equal to 29%; 2) subjecting the alloy flakes obtained in the above steps to hydrogen crushing without dehydrogenation to obtain a coarse powder with a high hydrogen content; 3) mixing the coarse powder with high hydrogen content obtained in the above step, a lubricant and an antioxidant, and then jet milling the mixture to obtain a fine powder; 4) orienting and pressing the fine powder obtained in the above steps to obtain a green compact; 5) The green compact obtained in the above steps is subjected to a first sintering and a second sintering to obtain a high remanence NdFeB magnet.

5. The preparation method according to claim 4, characterized in that: The magnet raw materials, measured by mass percentage, include: Nd: 27% to 29%, Co: 0 to 1%, Cu: 0 to 0.5%, B: 0.85% to 1.0%, Zr: 0 to 0.5% and the balance Fe; The hydrogen content of the coarse powder with high hydrogen content is 1500-3500 ppm.

6. The preparation method according to claim 4, characterized in that: The lubricant includes zinc stearate; The mass ratio of the lubricant to the coarse powder is (0.04-0.1):100; The antioxidant includes hexadecane-D34; The mass ratio of the antioxidant to the coarse powder is (0.04-0.1):

100.

7. The preparation method according to claim 4, characterized in that: The median particle size of the fine powder is 4.5 to 6.0 μm; The magnitude of the oriented magnetic field is 16000 to 22000 Gs; The pressure of the compression molding is 100-240 MPa.

8. The preparation method according to claim 4, characterized in that: The vacuum pressure of the first sintering is (2-8)×10 -2 Pa; The temperature of the first sintering is 1050-1070°C; The first sintering time is 3 to 10 hours.

9. The preparation method according to claim 4, characterized in that: The vacuum pressure of the second sintering is (2-8)×10 -2 Pa; The temperature of the second sintering is 1060-1090°C; The second sintering time is 3 to 8 hours.

10. The preparation method according to claim 4, characterized in that: After the second sintering, the process further includes primary aging and secondary aging treatment steps; The primary aging temperature is 850-950°C; The primary aging time is 3 to 5 hours; The temperature of the secondary aging is 440-560°C; The secondary aging time is 3 to 6 hours.

Citation Information

Cited By

  • Low-carbon high-purity neodymium-iron-boron magnet and preparation method thereof

    CN121460321A

  • Neodymium-iron-boron coarse powder, neodymium-iron-boron permanent magnet, and preparation method and use thereof

    CN122889539A